Interaction Between Coronavirus S-Protein and Human ACE2: Hints for Exploring Efficient Therapeutic Targets to Treat COVID-19. (February 2021) - Momtazi-Borojeni, Amir Abbas; Banach, Maciej; Reiner, Željko; Pirro, Matteo; Bianconi, Vanessa; Al-Rasadi, Khalid; Sahebkar, Amirhossein
With the global expansion of coronavirus disease 2019 (COVID-19) and the declaration of its outbreak as a Public Health Emergency of International Concern by the World Health Organization, there is an urgent need for vaccines and medicines to prevent and treat COVID-19. The responsible pathogen for the disease is the newly severe acute respiratory syndrome coronavirus (SARS-CoV) 2 belonging to the same family of viruses SARS-CoV and Middle East respiratory syndrome coronavirus that originally are zoonotic and have been associated with severe illness during the outbreaks in 2003 and 2012, respectively. The virulence of coronavirus strains is mainly associated with variations in surface proteins mediating cellular entry of the virus, which can help in finding effective therapeutic targets. In this review, we seek evidence showing the role of coronavirus spike protein (S-protein) and its potential cellular receptor, angiotensin-converting enzyme 2 (ACE2), during infection of coronaviruses, including the newly SARS-CoV-2 and its similar strain SARS-CoV. This review also discusses the therapeutic effect of inhibiting the renin–angiotensin system cascade, a target of ACE2, in patients having coronavirus with cardiovascular disease.